Comparative life cycle assessment of various ammonia production methods. (1st November 2016) - Bicer, Yusuf; Dincer, Ibrahim; Zamfirescu, Calin; Vezina, Greg; Raso, Frank
Abstract: In the present study, four different ammonia production methods are comparatively evaluated using life cycle assessment (LCA). The proposed ammonia production systems consist of an electrolyzer for hydrogen production and a Haber-Bosch plant for ammonia synthesis. The required energy for the systems are utilized from various resources namely hydropower, nuclear, biomass and municipal waste. Life cycle assessment methodology is used to identify and quantify environmental impacts in global warming potential, human toxicity and abiotic depletion categories of each method during the life cycle of the systems. The proposed non-conventional ammonia production options are comparatively assessed in terms of environmental impacts and both energy and exergy efficiencies as significant criteria for practical ammonia production applications. The LCA results for the ammonia production processes indicate that municipal waste incineration plant and hydropower based ammonia production methods have lower environmental impacts than other selected methods. The predicted greenhouse gas emissions (GHG) of hydropower, nuclear, biomass and municipal waste based ammonia production methods are calculated as 0.38 kg CO2 -eq, 0.84 kg CO2 -eq, 0.85 kg CO2 -eq and 0.34 kg CO2 -eq per kg of ammonia, respectively. The energy and exergy efficiencies of the systems are comparatively evaluated and as an indicator of improvement potential, sustainability index values are calculated accordingly. The energy efficiencies of the proposed ammonia production methods are determined to be 42.7%, 23.8%, 15.4% and 11.7%, respectively for hydropower, nuclear, biomass and municipal waste based options. The corresponding exergy efficiencies are found to be 46.4%, 20.4%, 15.5% and 10.3%, respectively for hydropower, nuclear, biomass and municipal waste based options.